Effect of different Intensity Electrotherapy on Functional Recovery in Patients with Knee Osteoarthritis - Fan, Zhijiao; Weiguang, Gao; Yubao, Ma; Shuyan, Qie (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2023)
Objective To explore the effects of different-intensity intermediate frequency therapy on functional recovery of patients with knee osteoarthritis.Methods Three-band electromagnetic waves of constant amplitude intermediate frequency electrotherapy group (Group A), interference electrotherapy group (Group B) and modulated intermediate frequency electrotherapy group (Group C) were used to treat knee osteoarthritis (KOA) patients, 20 min/time, 1 time/day and 5 days/week for four weeks. Other rehabilitation items were performed the same way. The rehabilitation therapy were evaluated by VAS score, Timed Up and Go test and balance ability.Results After 4 weeks of treatment, the treatment effects of the three groups were all significant compared with the pre-treatment. Among the three groups, the treatment effect of Group B was better than that of the other two groups, and there was no significant difference in the treatment effect between Group A and Group C.Conclusion According to thee. g.results, it is possible that the interference current is of a great action depth, and the "endogenous" low-frequency modulated intermediate frequency current possesses the advantages of both low and intermediate frequency, so with the intermediate frequency current getting through the high resistance of skin, the current effect of the low and intermediate frequency in the deep part of the human body can be achieved.Fragestellung Untersuchung der Wirkungen von Mittelfrequenz-Elektrotherapie mit unterschiedlicher Intensität auf die Funktionswiederherstellung bei Patienten mit Gonarthrose.Methode Patienten mit Gonarthrose erhielten Mittelfrequenz-Elektrotherapie mit elektromagnetischen Wellen (Drei-Band) mit konstanter Amplitude (Gruppe A), Interferenz-Elektrotherapie (Gruppe B) und modulierter Mittelfrequenz-Elektrotherapie (Gruppe C), jeweils 20 min/Sitzung, 1-mal täglich an 5 Tagen/Woche über einen Zeitraum von vier Wochen. Andere Rehabilitationsmaßnahmen wurden auf die gleiche Weise durchgeführt. Die Beurteilung der Rehabilitationsbehandlung erfolgte mittels VAS-Score, Timed Up and Go (TUG)-Test und Gleichgewichtsprüfung.Ergebnisse Nach vierwöchiger Behandlung fanden sich in allen drei Gruppen signifikante Therapieeffekte gegenüber dem Zustand vor der Behandlung. Im Vergleich der drei Gruppen war der Behandlungseffekt in der Gruppe B besser als in den beiden anderen Gruppen, und es gab keinen signifikanten Unterschied in der Wirkung der Behandlung zwischen Gruppe A und Gruppe C.Schlussfolgerung Die Ergebnisse weisen darauf hin, dass der Interferenzstrom eine große Wirktiefe aufweist und der „endogene“ niederfrequenzmodulierte Mittelfrequenzstrom die Vorteile von Nieder- und Mittelfrequenz vereint. Da der Mittelfrequenzstrom den hohen Widerstand der Haut durchdringt, kann mit Nieder- und Mittelfrequenz-Strom eine Tiefenwirkung erzielt werden.
Keywords: different intensity; electrotherapy; knee osteoarthritis; vas; function recovery